Rotary ultrasonic machining of carbon fiber-reinforced polymer: feasibility study - Feng, Q.; Cong, W. L.; Pei, Zhijian J.; Ren, C. Z. (My University, 2012)
Carbon fiber-reinforced polymer (CFRP) has been widely used in aircraft components, automotive parts, and sporting goods. Hole machining is the most frequently employed operation of secondary machining for fiber-reinforced composites. However, challenges (delamination, splintering, burr, short tool life, low machining precision, and low surface quality) still remain for their widespread applications. Rotary ultrasonic machining (RUM) is a non-conventional machining process that has been used to drill holes in composite materials. However, it has not been used to drill this type of CFRP. In this article, RUM is introduced into drilling holes in this type of CFRP for the first time. The feasibility to machine carbon fiber-reinforced epoxy using RUM is investigated experimentally. Chips, edge chipping, surface roughness, tool wear, and thrust force were measured. Effects of RUM process variables (rotation speed, vibration amplitude, and feedrate) on thrust force and surface roughness were studied. Results showed that RUM could be used to drill holes in CFRP with high productivity and low tool wear. A better surface was produced by higher rotation speed and lower feed rate.
Keywords: Carbon fiber-reinforced polymer; Drilling; Force; Rotary ultrasonic machining; Surface roughness; Tool wear